Automated MALDI Target Preparation Concept: Providing Ultra-High-Throughput Mass Spectrometry–Based Screening for Drug Discovery. (April 2019) - Winter, Martin; Ries, Robert; Kleiner, Carola; Bischoff, Daniel; Luippold, Andreas H.; Bretschneider, Tom; Büttner, Frank H.
Label-free, mass spectrometric (MS) deciphering of enzymatic reactions by direct analysis of substrate-to-product conversion provides the next step toward more physiological relevant assays within drug discovery campaigns. Reduced risk of suffering from compound interference combined with diminished necessity for tailored signal mediators emphasizes the valuable role of label-free readouts. However, MS-based detection has not hitherto met high-throughput screening (HTS) requirements because of the lack of HTS-compatible sample introduction. In the present study, we report on a fully automated liquid-handling concept built in-house to concatenate biochemical assays with matrix-assisted laser desorption/ionization time-of-flight closing this technological gap. The integrated reformatting from 384- to 1536-well format enables cycle times of 0.6 s/sample for automated spotting and 0.4 s/sample for MS analysis, matching the requirements of HTS compatibility. In-depth examination of spotting quality, quantification accuracy, and instrument robustness together with the implementation of a protein tyrosine phosphatase 1B (PTP1B) inhibitor screening (4896 compounds) demonstrate the potential of the heavily inquired HTS integration of the label-free MS readout. Overall, the presented data demonstrate that the introduced automation concept makes label-free MS-based readouts accessible for HTS within drug discovery campaigns but also in other research areas requiring ultrafast MS-based detection.